Optimizing peer review rounds in radiation oncology: a scoping review - Zhang, Jessica; Bayley, Conrad; Vaska, Marcus; Lee, Sangjune Laurence (Frontiers in Oncology, 2026)
PurposeIn radiation oncology (RO), peer review (PR) rounds are essential for ensuring quality care, enhancing team communication, and identifying areas for improvement in radiotherapy (RT) plans. However, time constraints, lengthy discussions, and imbalanced team contributions often hinder effective PR. This scoping review examined novel tools and processes to enhance PR efficiency and experience in modern academic centers.Materials and methodsWe queried six databases [MEDLINE (Ovid), EMBASE, PubMed, Cochrane Library, CINAHL, and MEDLINE (Ebsco)] and the gray literature, yielding 8,955 citations. Studies were excluded if they (1) were focused on comparisons involving paper-based rounds, (2) lacked clear relevance to PR processes in RT, or (3) did not explicitly address efficiency within PR activities.ResultsTwelve studies focusing on PR structure and efficiency-related processes were included. Of the identified, 11/12 explored various structural formats to improve facilitation, 5/12 discussed automated tools, and 2/12 evaluated checklists. Only half of studies reported a PR-associated time burden, with 2/12 reporting positive post-implementation changes. The remaining studies did not measure comparative times.ConclusionsThis scoping review reveals the lack of work on innovative approaches to optimize PR rounds in RO, despite the commonly reported participation barrier of high time commitment. Our findings highlight the importance of integrating automation in order to streamline facilitation methods and tools such as checklists to reduce inefficiency, given PR’s essential role in patient safety and clinical learning. Future research should prioritize the development and evaluation of time-saving strategies and tools for PR in RO workflow to optimize its sustainability and impact.